GSK3ß inhibitor CHIR 99021 modulates cerebral organoid development through dose-dependent regulation of apoptosis, proliferation, differentiation and migration. - Chloe Delepine; Vincent A Pham; Hayley W S Tsang; Mriganka Sur (PLoS ONE, 2021)
Cerebral organoids generated from human pluripotent stem cells (hiPSCs) are unique in their ability to recapitulate human-specific neurodevelopmental events. They are capable of modeling the human brain and its cell composition, including human-specific progenitor cell types; ordered laminar compartments; and both cell-specific transcriptional signatures and the broader telencephalic transcriptional landscape. The serine/threonine kinase, GSK3β, plays a critical role in neurodevelopment, controlling processes as varied as neurogenesis, morphological changes, polarization, and migration. In the generation of cerebral organoids, inhibition of GSK3β at low doses has been used to increase organoid size and decrease necrotic core. However, little is known of the effects of GSK3β inhibition on organoid development. Here, we demonstrate that while low dose of GSK3β inhibitor CHIR 99021 increases organoid size, higher dose actually reduces organoid size; with the highest dose arresting organoid growth. To examine the mechanisms that may contribute to the phenotypic size differences observed in these treatment groups, we show that low dose of CHIR 99021 increases cell survival, neural progenitor cell proliferation and neuronal migration. A higher dose, however, decreases not only apoptosis but also proliferation, and arrests neural differentiation, enriching the pool of neuroepithelial cells, and decreasing the pools of early neuronal progenitors and neurons. These results reveal new mechanisms of the pleiotropic effects of GSK3β during organoid development, providing essential information for the improvement of organoid production and ultimately shedding light on the mechanisms of embryonic brain development.